Clinical outcomes of arthroscopic suture fixation combined with loop plate vs. posterior approach open reduction and cannulated screw fixation for treating tibial avulsion fractures of the posterior cruciate ligament: a retrospective study - Zhang,Lan; Guo,Dan (PeerJ, 2024)
Background Comparison of the efficacy of arthroscopic suture fixation combined with loop plate vs. the posterior approach involving open reduction and intramedullary nail fixation in treating posterior cruciate ligament tibial avulsion fractures (PCLTAFs). Methods A retrospective analysis was conducted on the clinical data of patients diagnosed with PCLTAF who were admitted to Northern Jiangsu People’s Hospital between June 2019 and March 2022. Based on distinct surgical procedures, the patients were categorized into two groups: arthroscopic group (33 cases), involving a single bone tunnel, high-strength suture, loop plate, and anchor screw fixed under arthroscopy, and open reduction and internal fixation (ORIF) group (13 cases), involving a modified posterior medial approach and fixation using 1–2 cannulated screws. Key parameters, including surgical duration, postoperative fracture alignment, fracture-healing duration, range of motion changes, postoperative Lysholm scores, and VAS scores were documented and compared between the two groups. Results The study cohort comprised 46 patients, with 28 males and 18 females, and the median age was 29 years old (range: 15–69). There were no significant differences in the baseline characteristics, including knee Lysholm scores, between the two groups. The arthroscopic group exhibited significant improvement in all eight Lysholm score indicators (all P < 0.001). The total Lysholm score also exhibited significant improvement before and after surgery in both groups (P < 0.001). Following surgery, the arthroscopic group demonstrated improvements in all indicators, but had a slightly longer operating time compared to the ORIF group. No significant differences were observed in the Lysholm scores for the knee joint between the two patient groups before and after surgery (P > 0.05). Conclusions Arthroscopic suture fixation in conjunction with looped plate binding can significantly improve knee function and clinical effect for patients in the treatment of PCLTAF, promotingearly postoperative functional recovery of patients.
Keywords: Adolescent; Arthroscopic suture fixation; Knee instability; Open reduction and internal fixation; Posterior cruciate ligament; Tibial avulsion fracture